How do small firms use ICT for business purposes? A study of Swedish technology-based firms. (8th March 2010) - Parida, Vinit; Westerberg, Mats; Ylinenpaa, Hakan
This study examines the extent to which Information and Communication Technology (ICT) capability is possessed and utilised by technology-based small firms and investigates the contingent effect of firm size and age on ICT capability. The empirical base is a survey with data from 291 technology-based small Swedish firms. The result suggests that technology-based small firms are high users of ICT in several areas. Regarding contingency effects, firm size was related to significant differences in the utilisation of ICT. Although the smallest firms as a whole use ICT less, a substantial part of them are high users.